2023
DOI: 10.1111/jsap.13619
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cannabidiol use in pets according to a national survey in the USA

Abstract: Objectives Conduct an online questionnaire to understand the motivations and perceptions about cannabidiol use in companion animals in the USA. Materials and Methods Data from a USA population sample who owned a pet were gathered using an online questionnaire. Perception of cannabidiol efficacy was analysed for independence against explanatory variables using the Pearson chi‐square test, followed by a binary logistic regression. Results A total of 1238 participants completed the survey; 356 had administered ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The ambient scent of lavender may be beneficial as a treatment for travel-induced arousal in dogs [ 79 ]. A recent study revealed that more than 75% of surveyed dog owners in the U.S.A. have administered cannabidiol (CBD), a phytocannabinoid found in hemp, to their pets [ 80 ], and it cannot be ruled out that some have also administered it to young dogs. The primary reason participants administered CBD to their pets was its anxiolytic and calming effects, which addressed conditions such as separation anxiety, nervousness, aggressiveness, and situations such as fireworks-related fear and travel.…”
Section: Use Of Herbal Medicine In Puppiesmentioning
confidence: 99%
“…The ambient scent of lavender may be beneficial as a treatment for travel-induced arousal in dogs [ 79 ]. A recent study revealed that more than 75% of surveyed dog owners in the U.S.A. have administered cannabidiol (CBD), a phytocannabinoid found in hemp, to their pets [ 80 ], and it cannot be ruled out that some have also administered it to young dogs. The primary reason participants administered CBD to their pets was its anxiolytic and calming effects, which addressed conditions such as separation anxiety, nervousness, aggressiveness, and situations such as fireworks-related fear and travel.…”
Section: Use Of Herbal Medicine In Puppiesmentioning
confidence: 99%
“…The use of Cannabis Sativa hemp strains for cannabinoid treatment has gained popularity among pet owners and veterinarians alike over the past 10 years [1,2]. Cannabis Sativa in the United States that has less than 0.3% delta 9-tetrahydrocannabinol (THC) is considered hemp, and is federally legal, creating a burgeoning market of pet supplements made from these low THC cultivars [3].…”
Section: Introductionmentioning
confidence: 99%